Strong neel ordering and luminescence correlation in a two-dimensional antiferromagnet - Zhou, Yongheng (2023)
Magneto-optical effect has been widely used in light modulation, optical sensing, and information storage. Recently discovered 2D van der Waals layered magnets are considered as promising platforms for investigating novel magneto-optical phenomena and devices, due to the long-range magnetic ordering down to atomically thin thickness, rich species, and tunable properties. However, majority 2D antiferromagnets suffer from low luminescence efficiency which hinders their magneto-optical investigations and applications. This work uncovers strong light-magnetic ordering interactions in 2D antiferromagnetic MnPS3 using a newly-emerged near-infrared photoluminescence (PL) mode far below its intrinsic bandgap. This ingap PL mode shows strong correlation with the Neel ordering and persists down to monolayer thickness. Combining the density-functional theory (DFT), scanning transmission electron microscopy (STEM), and X-ray photoelectron spectroscopy (XPS), this work illustrates the origin of the PL mode and its correlation with Neel ordering, which can be attributed to the oxygen ion-mediated states. Moreover, the PL strength can be further tuned and enhanced using ultraviolet-ozone (UVO) treatment. The studies offer an effective approach to investigate light-magnetic ordering interactions in 2D antiferromagnetic semiconductors.